PENGENALAN BUDAYA JEPANG DAN PENGUATAN KEMAMPUAN BAHASA JEPANG MELALUI JLPT PADA SISWA MAN 1 PASURUAN - Savitri, Laily Amalia; Cahyono, Agus Budi; Efrizal, Efrizal (Faculty of Cultural Studies, Universitas Brawijaya, 2022)
Japanese is one of the foreign languages that many students learn in Indonesia, including at MAN1 Pasuruan. Students of MAN 1 Pasuruan have a great curiosity about Japanese culture, especiallyabout the lives of Japanese high school students, shodou 'Japanese calligraphy', Japanese language,and JLPT (Japanese Language Proficiency Test). However, learning Japanese at MAN 1 Pasuruanhas limited learning time, so that during learning hours it is more focused on teaching basicJapanese, while teaching about Japanese culture and JLPT is still very necessary. Therefore, thiscommunity service activity aims to increase students' understanding and interest in Japanese cultureand language so that students can measure their own learning success and Japanese language skillswith JLPT test. This community service activities were carried out at MAN 1 Pasuruan using ablended method which was attended by 50 students (40 students via online and 10 students viaoffline) from class X Language, XI Language, and XII Language by introducing Japanese highschool life, simulations of JLPT test, as well as demonstrations and shodou workshops by nativespeakers and experts who expert in their fields. The high activity and enthusiasm of students showsthat this community service program is very much needed by MAN 1 Pasuruan to accommodate theneeds and to increase students' interest in learning Japanese language and culture that has beenlearned during teaching and learning activities in class.Keywords: Japanese culture, Japanese high school student life, shodou, Japanese language, JLPT